Analysis Of Factors Influencing Willingness to Pay for Premium Subscription Features E-Commerce - Aulia Febrianti; Corry Yohana; Ringga Sentagi Asa (Fakultas Ekonomi Universitas Simalungun, 2026)
This study was conducted to analyze the influence of electronic word of mouth, perceived value, brand awareness, and attitude on consumers' willingness to pay for Shopee VIP features. This study uses a quantitative approach with data collection through an online survey. Data was collected from 230 respondents who were Generation Z born between 1997 and 2012, residing in DKI Jakarta, having active Shopee accounts, and knowing about and intending/willing to subscribe to the Shopee VIP premium feature. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings of this study indicate that all hypotheses were accepted. Electronic word of mouth, perceived value, brand awareness, and attitude were proven to have a positive and significant effect on willingness to pay